Wireless real‐time monitoring of malolactic fermentation in wine barrels: the Wireless Sensor Bung system. (21st December 2012) - Di Gennaro, S.F.; Matese, A.; Primicerio, J.; Genesio, L.; Sabatini, F.; Di Blasi, S.; Vaccari, F.P.
Abstract Background and Aims Malolactic fermentation (MLF) is a metabolic process promoted in wine by lactic acid bacteria, which can improve wine quality. The MLF, however, must be properly monitored and handled in a timely manner as the bacteria remaining in the wine can produce off‐flavours. This work describes the Wireless Sensor Bung (WSB), a system for monitoring remotely wine parameters in barrel and a methodology for monitoring MLF in real time. Methods and Results A wireless system to measure wine deacidification because of MLF was developed. The WSB was calibrated and tested in an experiment in a commercial cellar to assess the system performance in a barrel. The system enabled an exhaustive monitoring of wine deacidification associated with MLF. Conclusions The WSB system was demonstrated to be an effective tool for monitoring remotely MLF in barrel. Significance of the Study The WSB provides timely information on the completion of MLF, so that lactic acid bacteria can be eliminated from wine before they produce undesirable metabolites.